2021
DOI: 10.1109/tim.2021.3067943
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of P300 Detection by Multiscale-CNN

Abstract: P300-based spelling system is one of the most popular brain-computer interface applications. Its success largely depends on performance, including the information transmission rate (ITR) and detection rate (i.e., accuracy). To achieve good performance, we proposed a multi-scale convolutional neural network (MS-CNN) model, which consists of seven layers. First, an upfront dataset was used to train the MS-CNN, aiming to obtain a subject-unspecific model (universal model) for P300 detection. Second, this universa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…We found that all three spatial attention maps share two common channels (Cz and CPz), and the enhanced electrodes were located roughly in the central and parietal lobes of the brain, indicating that the attention module was able to capture the spatial features of P300. Furthermore, the learned spatial attention maps generally accords with those of previous studies [15], [23], [24].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found that all three spatial attention maps share two common channels (Cz and CPz), and the enhanced electrodes were located roughly in the central and parietal lobes of the brain, indicating that the attention module was able to capture the spatial features of P300. Furthermore, the learned spatial attention maps generally accords with those of previous studies [15], [23], [24].…”
Section: Discussionsupporting
confidence: 86%
“…However, it has a low symbol recognition rate in the first 5 or even 10 repetitions, leading to a low information transfer rate (ITR). To further increase the symbol recognition rate in the first 5 repetitions, Wang et al [24], who have crowned champions of the P300based BCI competition in the 2019 World Robot Conference, proposed Multiscale-CNN to enhance the performance of P300 detection. Three temporal kernels at different scales were applied on its temporal convolution layer to obtain discriminative time features.…”
Section: Introductionmentioning
confidence: 99%
“…Erdogan et al analyzed the response of specific users to the spelling paradigm and determined the most appropriate P300 detection band for them [ 93 ]. In recent years, Wang et al used a multi-scale convolutional neural network (MS-CNN) to train a general decoding model and then adjusted the general model by using part of the data of specific subjects through transfer learning to obtain a customized decoding model [ 94 ]. In addition, Li et al proposed a TrAdaBoost algorithm based on cross-validation and an adaptive threshold (CV-T-TAB).…”
Section: Personalized Bci Applicationmentioning
confidence: 99%
“…Through averaging the EEG signal time-locked to fixations on target object, a relatively late component in FRP associated with P300 potential was observed [14], [15], which is typically related to cognitive functions such as attention and object identification. Considering the ability of P300 in discriminating target stimulus and distractors [16], it can be inferred that the fixation-related P300 could provide discriminative information in terms of FRP classification. For example, Brouwer et al achieved satisfactory single-trial FRP classification accuracy and revealed the reliable discrimination of a P300-liked FRP component [11].…”
Section: Introductionmentioning
confidence: 99%